Reliability and factor structure of the General Health Questionnaire-12 among university students - Ibrahim, Normala; Jamil@Osman, Zubaidah; Naing@Noorjan, Khin Ohnmar; Ismail, Siti Irma Fadhilah; Phang , Cheng Kar; Mukhtar, Firdaus; Mohd Sidik, Sherina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2014)
The 12- item General Health Questionnaire (GHQ-12) has been translated into many languages and widely used in different settings and countries. Its reliability and psychometric properties were extensively studied in many population groups which suggested that it measures psychological distress in multidimensional construct. Objective: The objective of this study was to assess the reliability and factor structure of the Bahasa Malaysia version of the GHQ-12 among university students attending a health program at a Malaysian public university. Method: The cross sectional survey was conducted on 306 undergraduate students aged between 18 to 27 years old who visited the booth set up for mental health screening at a health program. The screening was conducted using a self-administered, validated Bahasa Malaysia version of GHQ-12 questionnaire. Results: Using exploratory factor analysis, the Bahasa Malaysia version of GHQ-12 was found to have a three factor structures namely depressive symptoms, self-esteem and perceived abilities which accounted for 58% of the item variance. The overall Cronbach’s alpha coefficient of the scale was found to be high (0.84) with each factor having acceptable inter-item consistency ranging from 0.61 to 0.82. Conclusion: The findings of the study show that the Bahasa Malaysia version GHQ-12 is reliable and has good structural characteristics. It can assess a few domains of the psychological status of university students. It also helps in providing more information on the domain which may become a focus target of intervention in the prevention of mental illness.